Morphological Awareness Intervention With Kindergarteners and First and Second Grade Students From Low SES Homes: A Small Efficacy Study. (January 2014) - Apel, Kenn; Diehm, Emily
We investigated the efficacy of a morphological awareness intervention on the morphological awareness and reading skills of students from low-socioeconomic-status homes; we also examined whether the intervention was similarly effective for intervention students who differed in their initial morphological awareness abilities. The 8-week intervention was designed to increase awareness of affixes and the relations between base words and their inflected and derived forms for kindergarteners ( n = 27) and first- ( n = 22) and second-grade ( n = 26) students. Students randomly assigned to the small group intervention were provided instruction four times a week, 25 min a day, whereas students assigned to the control group received "business as usual." Kindergarten and first- and second-grade students receiving the intervention showed statistically significant gains in morphological awareness with large effect sizes on most measures. Students in all three grades who received the intervention demonstrated nonsignificant gains in literacy abilities with null to small effect sizes. Further, students with low morphological awareness abilities at the onset of the study demonstrated similar gains from the intervention as their peers with typical morphological awareness abilities. Our results suggest that explicit morphological awareness instruction may produce gains of practical importance to young elementary students at risk for future literacy difficulties.